Analysis of The Effectiveness of Accounts Receivable Management Through the Accounts Receivable Turnover Ratio at PT PLN (Persero) in 2023–2024 - Adelia Ayu Sinorowenti; Riska Agustin (Universitas Islam Negeri (UIN) Salatiga, 2025)
Accounts receivable management is an important aspect in maintaining the financial stability of a company, especially for PT PLN (Persero), which has a large customer base with a postpaid payment system. This study aims to analyze the effectiveness of accounts receivable management through the accounts receivable turnover ratio at PT PLN (Persero) in 2023–2024. The research method used is quantitative descriptive with a case study approach, based on secondary data in the form of financial reports for the 2023–2024 period. The analysis was conducted through the receivable turnover ratio, average receivables, and collection periods. The results show that PT PLN (Persero)'s receivable turnover ratio was around 12.91 times in 2023 and increased to 12.96 times in 2024, which is classified as “sufficient” according to industry standards. Meanwhile, the collection period improved from 30 days in 2023 to 29 days in 2024. This condition reflects the effectiveness of receivables management, marked by improvements in the billing system, the implementation of digital payments through the PLN Mobile application, and the diversification of payment channels that support the company's cash flow efficiency. The conclusion of this study is that the implementation of proper accounts receivable management can reduce the potential for bad debts, increase liquidity, and support the company's operational sustainability. This study is expected to provide practical contributions to PT PLN (Persero) and other utility companies in strengthening their digital-based accounts receivable management strategies